Pengaruh Fasilitas Ruang Tunggu Terhadap Kepuasan Penumpang di Bandar Udara Sultan Thaha Jambi - Rizki Gunawan (CV. Rayyan Dwi Bharata, 2024)
In achieving passenger satisfaction there are several things and requirements that must be considered and fulfilled by airport managers, especially waiting room facilities. Factors that must be considered by officers are spatial planning, space planning, furniture equipment, lighting and color, messages delivered free of charge and supporting elements. In this case all airport officers must be able to guarantee passenger satisfaction. This study aims to determine the effect of waiting room facilities on passenger satisfaction at Sultan Thaha Jambi Airport. This research uses quantitative methods. Respondents in this study amounted to 100 passengers at Sultan Thaha Jambi Airport. Data obtained through the distribution of questionnaires offline. The data analysis technique uses Simple Linear Regression Test, T Test, and Determination Coefficient Test. The results of this study indicate that there is an effect of waiting room facilities on passenger satisfaction at Sultan Thaha Jambi Airport. Evidenced by the results of the T Test (Partial), it is known that T count is 19.048 1.660 with a significance value obtained of 0.01 0.05, this states that partially the variable quality of the waiting room facilities affects the passenger satisfaction variable and the results of the Coefficient of Determination Test show a result of 78.7%, which means that the quality of the waiting room facilities influences passenger satisfaction while the remaining 21.3% is influenced by other factors not examined.